Formalin Resistant Fungi Isolated from Cadavers at a Medical School’s Dissection Hall in Malaysia - Herlina Anton; Husni Al-Ghoshae; Manah Chandra; Mohammaed Faez Baobaid; Thin Aung; Haziq Hazman; Mohamad Al-Hoot; AbdelKodose Al-Kabsi (Asian Journal of Medicine & Health Sciences, 2022)
Introduction: Utilization of the cadavers as part of teaching methodology in anatomy are equally important either for undergraduate or postgraduate students. Microorganisms such as bacteria (Mycobacterium tuberculosis) were previously reported to have a survival rate up to 36 days after the death of the host. Recent studies have suggested the difference in the degree of efficacy in formalin to halt the growth of different microorganisms in the formalin fixed tissues. Hence this study aims to determine the presence of specific bacteria and / or fungi on the surface of a formalinfixed cadavers. Methodology: Swab samples were taken from the nose, oropharynx, ear, axilla, and anal canal of five cadavers in the dissection hall at ainternational Medical School (IMS) of Management & Science University (MSU). Samples were incubated at 37o for 24-48 hours in various culture media which includes blood agar, nutrient agar, chocolate agar, and MacConkey agar for bacterial culture and Sabouraud dextrose agar (SDA) for fungal culture. Blood agar plates were incubated in anaerobic jars to create low oxygen conditions to allow the growth of anaerobic bacteria. The culture media were taken outside the incubators and put under room temperature and observed for another 7 days to observe for any fungal growth. Results: Fungal growth was found in two cadavers in the regions of the ear and oropharynx. Fungal growths were stained with lactophenol cotton blue solution and examined under the light microscope. No bacterial growth was detected in this study. Conclusion: This study showed that the growth of fungus corresponds with Aspergillus species isolated from two cadavers.